(untitled) (Indian Journal of Hill Farming, 2022)
The Uttarakhand Himalaya has a rich agro-climate for cultivating various kinds of fruits at different altitudes. Four agro-climatic zones – plain regions and the river valleys (subtropical), lower-middle zone (sub-tropical), upper-middle zone (temperate), and the highlands (temperate and cold) comprised it. This paper examines the typology, potential, and development of fruit cultivation in the Uttarakhand Himalaya. Data were gathered from secondary sources - the Directorate of Horticulture and Food Processing, Horticulture Bhawan, Chaubatiya, Uttarakhand. Further, the participatory approach was applied to validate the area, production, and productivity of fruits after rapid field visits to fruit-growing areas. Based on the above-mentioned agro-climatic conditions, fruit types and fruit growing areas were correlated as temperate fruits (apple and pear) in the highlands, nut and stone fruits in the middle and high altitudes, citrus fruits in the valley regions, and sub-tropical fruits (mango, guava, and litchi) in the valley and the plain regions. The area and production of the principal fruits were gathered and the productivity of the fruits was noticed. The author has categorized fruit cultivating areas into three zones according to the agro-climate and the area, production, and productivity of fruits. These zones are named developed, developing, and potentials. The present study is original. It presents new findings in the fields of fruit cultivation in the Uttarakhand Himalaya. If intensive fruit cultivation is carried out by providing all the infrastructural facilities including market facilities, it will enhance the income and livelihoods of the rural people.